2003
DOI: 10.1074/jbc.m208437200
|View full text |Cite
|
Sign up to set email alerts
|

Imprint Control Element-mediated Secondary Methylation Imprints at the Igf2/H19 Locus

Abstract: Understanding the molecular basis of monoallelic expression as observed at imprinted loci is helpful in understanding the mechanisms underlying epigenetic regulation. Genomic imprinting begins during gametogenesis with the establishment of epigenetic marks on the chromosomes such that paternal and maternal chromosomes are rendered distinct. During embryonic development, the primary imprint can lead to generation of secondary epigenetic modifications (secondary imprints) of the chromosomes. Eventually, either t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…Paternal-allele-specific methylation was maintained at the H19 locus upon deletion of the DMD in neonatal liver (Fig. 6B, bottom panel, lanes 8 to 11, and data not shown), as was also observed by Srivastava et al upon deleting the DMD in another somatic tissue (42,43).…”
Section: ⌬38kb-5h19supporting
confidence: 59%
See 1 more Smart Citation
“…Paternal-allele-specific methylation was maintained at the H19 locus upon deletion of the DMD in neonatal liver (Fig. 6B, bottom panel, lanes 8 to 11, and data not shown), as was also observed by Srivastava et al upon deleting the DMD in another somatic tissue (42,43).…”
Section: ⌬38kb-5h19supporting
confidence: 59%
“…Neither of the conditional deletions disrupted H19 imprinting of the paternal allele. H19 silencing and the paternal-allele-specific methylation of the H19 promoter, which is hypomethylated in sperm and is hypermethylated in differentiated tissues, were retained despite the absence of the upstream sequence (data not shown) (42,43). Thus, the DMD is required to maintain maternal Igf2 repression but not necessary to maintain the silencing of paternal H19 once the imprinted state is fully established.…”
Section: Molecular Analyses Of the Endogenous Wild-type And Mutantmentioning
confidence: 99%
“…At the same time, the methylated paternal DMR induces epigenetic changes at the H19 promoter that silence H19 expression (4, 9, 40). These epigenetic changes are developmentally programmed, and once established, they can maintain repression of the paternal H19 even in the absence of the DMR (39,40).Beyond the DMR's role in regulating transcription of the two genes, genetic evidence is consistent with the notion that the DMR has a third distinct function: it is at least part of the imprinting control element (ICE) for the H19 and Igf2 genes.That is, the element appears to be necessary for marking the chromosomal origin of the two genes and of H19 transgenes (11,23,44). Furthermore, molecular studies have shown that the H19DMR is methylated in sperm but not in oocytes and the differential methylation is maintained during the global changes in methylation patterns associated with early development (3, 14, 45).…”
mentioning
confidence: 49%
“…At the same time, the methylated paternal DMR induces epigenetic changes at the H19 promoter that silence H19 expression (4,9,40). These epigenetic changes are developmentally programmed, and once established, they can maintain repression of the paternal H19 even in the absence of the DMR (39,40).…”
mentioning
confidence: 99%
“…The germ line marks that permit monoallelic gene expression are still not fully understood, and appear to be added to specific imprinted loci at variable stages of gametogenesis and post-fertilisation development (reviewed by Allegrucci et al 2005). There is also evidence that the initial germ line 'imprints' are reinforced or completed after fertilisation (Srivastava et al 2003). The dynamics of imprint development is of interest due to the increasing evidence that both in vivo and in vitro influences on the preimplantation embryo can alter genomic imprinting with a range of developmental consequences (reviewed by Swales & Spears 2005).…”
Section: Introductionmentioning
confidence: 99%